Cochlear Implantation in Organ Transplant Recipients. Issue 9 (October 2018) - Suhling, Marie-Charlot; Lenarz, Thomas; Teschner, Magnus
Abstract : Objective: Immunosuppressed individuals who have undergone organ transplants, especially children, pose particular challenges in terms of treatment. The aim of this study was to analyze the postoperative complication rate of organ transplant recipients who have also received a cochlear implant (CI). Study Design: Retrospective case series. Setting: Tertiary referral center. Intervention: The case series includes 13 kidney, liver, lung, and heart transplant patients. Age at treatment ranged from 2 to 71 years, with a total of 17 CIs. Main Outcome Measures: Postoperative complications were classified into major and minor, early (within 3 mo postoperatively) and late (>3 mo postoperatively). The results were compared with those for 13 1:1 matched pairs obtained and from our database and a healthy patient collective from our department. Results: The global postoperative complication rate was 29.4%. The proportion of patients suffering major complications was 17.6%, with 17.6% having minor complications. Complications that occurred early accounted for 13.3%, and late for 26.7%. No adults, and 33.0% of children, showed any complications after cochlear implantation. The global complication rate (29.4%) was significantly increased compared with the matched pairs (0%, p = 0.013) and department data (13.8%, p = 0.006; Cramers v = 0.102). Conclusion: This study demonstrates that organ transplant recipients, and especially children, are at increased risk of postoperative complications after cochlear implantation in comparison with healthy CI recipients.